Correlation of Plasma MMP-1 and TIMP-1 Levels and the Colonic Mucosa Expressions in Patients with Ulcerative Colitis. (9th November 2009) - Wang, Ying-De; Tan, Xiao-Yan; Zhang, Ke
Abstract : Background . Both plasma and mucosal levels of matrix metalloproteinase-1 (MMP-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1) have been shown to be independently correlated with ulcerative colitis (UC), but their relationship with each other and to disease severity remains unclear. This study aims to evaluate the relationship between colonic mucosal and plasma levels of MMP-1 and TIMP-1 with each other and with the severity of ulcerative colitis (UC). Methods . Colonic mucosal lesions and venous blood samples were collected from 30 patients with UC and 15 normal subjects. Real-time reverse transcription-PCR and immunohistochemistry were used to determine colonic mucosal MMP-1 and TIMP-1 expression; ELISA was used to measure plasma levels of MMP-1 and TIMP-1. Results . Expression of colonic mucosal and plasma MMP-1 and TIMP-1 in patients with UC was significantly higher than that of controls (P < .05 ), and was positively correlated with disease severity (P < .05 ). Plasma MMP-1 and TIMP-1 levels were well correlated with their corresponding expression in colonic mucosa (P < .05, r = 0.805 and 0.908). Conclusion . Plasma MMP-1 and TIMP-1 levels reflect their colonic mucosal expression to some extent in patients with UC. Plasma MMP-1 and TIMP-1, in particular, demonstrate the potential to become biomarkers to clinically diagnose UC, predict its severity, and guide further therapy.